2007
DOI: 10.1017/s0952523807070198
|View full text |Cite
|
Sign up to set email alerts
|

Robust syntaxin-4 immunoreactivity in mammalian horizontal cell processes

Abstract: Horizontal cells mediate inhibitory feed-forward and feedback communication in the outer retina; however, mechanisms that underlie transmitter release from mammalian horizontal cells are poorly understood. Toward determining whether the molecular machinery for exocytosis is present in horizontal cells, we investigated the localization of syntaxin-4, a SNARE protein involved in targeting vesicles to the plasma membrane, in mouse, rat, and rabbit retinae using immunocytochemistry. We report robust expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
57
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 102 publications
(71 reference statements)
12
57
0
Order By: Relevance
“…1B,C), as previously reported (Hirano et al, 2007;Morgans et al, 1996). Syntaxin 3 was also detected in the calycal processes (CPs) (Fig.…”
Section: Resultssupporting
confidence: 85%
“…1B,C), as previously reported (Hirano et al, 2007;Morgans et al, 1996). Syntaxin 3 was also detected in the calycal processes (CPs) (Fig.…”
Section: Resultssupporting
confidence: 85%
“…These data suggest LRIT1 is likely not expressed in cone OFF bipolar cells. Previous work has shown that the horizontal cell markers calbindin, syntaxin-4, and GluA2 all localize distal to PNA, which is similar to our data for LRIT1 and PNA (133,136), suggesting LRIT1 may be localized on the horizontal cell invaginating contacts at cone terminals. Our observed LRIT1 staining pattern with mGluR6 and GPR179 is consistent …”
Section: Chapter IV Discussionsupporting
confidence: 91%
“…Prior work has shown that the ON bipolar cell markers LRIT3 (78), NYX (63,73), mGluR6 (130), and TRPM1 (131) show a similar localization. Previous studies also showed that the horizontal cell markers calbindin and syntaxin-4 localize adjacent to piccolino or RIBEYE crescents, respectively (132,133). Piccolino is another synaptic ribbon marker shown to colocalize with RIBEYE (134,135).…”
Section: Chapter IV Discussionmentioning
confidence: 90%
“…The question addressed was if primate horizontal cells may employ a feed-forward pathway from horizontal cells directly to cone bipolar cells. Syntaxin-4 has been shown to be expressed by horizontal cells in different mammals and it was used as an indicator for vesicular GABA release in horizontal cells [35]. In macaque monkeys, syntaxin-4 was found in HI and HII horizontal cells postsynaptic to all photoreceptor types, but highly enriched beneath short (S-) wavelength sensitive cones, co-localized with dendritic processes of HII horizontal cells.…”
Section: Introductionmentioning
confidence: 99%